Preaudit data collection on commencing warfarin therapy in paediatric congenital heart disease patients to aid guideline production. Issue 5 (22nd April 2012) - Moore, E; Gage, S; Forsey, J; Harrington, C; Tometzki, A
Abstract : Objective: To assess the safety and efficacy of warfarin loading, in our paediatric congenital heart disease patients, using the current protocols. By retrospective review of the data collected, implement change in line with the National Patient Safety Agency (NPSA) Alert 18 safety indicators, 1 by formulating a departmental and regional guideline. Method: A data collection sheet was designed and reviewed by the paediatric cardiac pharmacist, a cardiac nurse specialist and a paediatric cardiology registrar. The data collection was conducted by a medical student during the period of 28th June 2010 and 7th July 2010. All paediatric congenital heart disease inpatients during the study period were included in this preaudit data collection exercise. A retrospective study of patient medical notes and the paediatric congenital heart database (Heartsuite) was conducted between 1st July 2009 and 31st May 2010. The data collection reviewed; documentation in the patient's medical notes regarding commencement of warfarin, the loading dose given, the loading regimen over days 2–7 and the international normalised ratio (INR) target at discharge. Results: There were eight new patients commenced on warfarin during the study period; seven postsurgery and one post pulmonary embolism. Documentation in the medical notes was variable; no documented reason why warfarin started or that verbal or written information given to patient/parents, the majority of loading doses used were documented and all of the INR results post surgery was detailed. As regards loading and target ranges; less than half of patients complied with the day 2–7 loading regimen protocol during the study period but at discharge seven out of the eight patients were in target range. The post discharge INR results were 46% within range, only one patient had an INR of greater than five and none had an INR greater than 8. Conclusion: This data collection has highlighted that documentation and prescribing could be improved by the production of a comprehensive guideline that highlights the NPSA recommendations in Alert 18 that can be used within our department and regionally. This data collection has also shown that less than half of patients adhered to the current loading regimen that was used during the collection period, so our loading regimen used will need to be reviewed. Despite this there were no reports of adverse events such as major bleeding and only one patient had an INR greater than 5. Once a guideline has been written and approved, all of the standards outlined in this data collection will need to be re-audited.